Early fibrotic niches establish tumour-permissive microenvironments - Erik C. Cardoso; Hyeyoung Lee; Frances J. England; Hyunjin Cho; Robin Lu; Sagar S. Varankar; Moo Suk Park; Natasha Rekhtman; Bon-Kyoung Koo; Benjamin D. Simons; Jinwook Choi; Joo-Hyeon Lee (Nature, 2026)
Abstract Pathologic transformation represents a critical yet poorly defined window during which mutant epithelial stem cells actively construct the microenvironment that enables tumour initiation 1,2 . Here using integrated single-cell, spatial and functional analyses, we define the earliest multicellular events that licence this transition following oncogenic activation in the lung. Kras G12D -mutant alveolar type II cells rapidly adopt regenerative-like states that act as signalling hubs, orchestrating coordinated stromal and immune reprogramming while enhancing epithelial plasticity. Through secretion of amphiregulin, mutant epithelial cells activate EGFR signalling in adjacent fibroblasts, inducing a fibrotic, injury-like programme. Reprogrammed fibroblasts, in turn, expand and reprogramme alveolar macrophages, amplifying inflammatory signalling and reinforcing epithelial plasticity. These reciprocal interactions establish a self-sustaining epithelial–stromal–immune circuit that generates a tumour-permissive niche before malignant outgrowth. Disruption of the amphiregulin–EGFR axis prevents early niche formation and abrogates tumour initiation. Conservation of this programme in KRAS G12D -inducible human alveolar organoids and early-stage lung adenocarcinoma tissues identifies epithelial–microenvironment communication as a therapeutically actionable vulnerability and suggests that intercepting niche formation may prevent progression to treatment-resistant disease.